Transcription-Coupled Translation Control of AML1/RUNX1 Is Mediated by Cap- and Internal Ribosome Entry Site-Dependent Mechanisms - Pozner, Amir (American Society for Microbiology, 2000)
AML1/RUNX1 belongs to the runt domain transcription factors that are important regulators of hematopoiesis and osteogenesis. Expression of AML1 is regulated at the level of transcription by two promoters, distal (D) and proximal (P), that give rise to mRNAs bearing two distinct 5′ untranslated regions (5′UTRs) (D-UTR and P-UTR). Here we show that these 5′UTRs act as translation regulators in vivo. AML1 mRNAs bearing the uncommonly long (1,631-bp) P-UTR are poorly translated, whereas those with the shorter (452-bp) D-UTR are readily translated. The low translational efficiency of the P-UTR is attributed to its length and the cis-acting elements along it. Transfections and in vitro assays with bicistronic constructs demonstrate that the D-UTR mediates cap-dependent translation whereas the P-UTR mediates cap-independent translation and contains a functional internal ribosome entry site (IRES). The IRES-containing bicistronic constructs are more active in hematopoietic cell lines that normally express the P-UTR-containing mRNAs. Furthermore, we show that the IRES-dependent translation increases during megakaryocytic differentiation but not during erythroid differentiation, of K562 cells. These results strongly suggest that the function of the P-UTR IRES-dependent translation in vivo is to tightly regulate the translation of AML1 mRNAs. The data show that AML1 expression is regulated through usage of alternative promoters coupled with IRES-mediated translation control. This IRES-mediated translation regulation adds an important new dimension to the fine-tuned control of AML1 expression.